Microbial Community Shifts in Response to Acid Mine Drainage Pollution Within a Natural Wetland Ecosystem - Aguinaga, Oscar E.; McMahon, Anna; White, Keith N.; Dean, Andrew P.; Pittman, Jon K. (Frontiers in Microbiology, 2018)
Natural wetlands are known to play an important role in pollutant remediation, such as remediating acid mine drainage (AMD) from abandoned mine sites. However, many aspects of the microbiological mechanisms underlying AMD remediation within wetlands are poorly understood, including the role and composition of associated microbial communities. We have utilised an AMD-polluted river-wetland system to perform rRNA sequence analysis of microbial communities that play a role in biogeochemical activities that are linked to water quality improvement. Next-generation sequencing of bacterial 16S rRNA gene amplicons from river and wetland sediment samples identified variation in bacterial community structure and diversity on the basis of dissolved and particulate metal concentrations, sediment metal concentrations and other water chemistry parameters (pH, conductivity), and wetland plant presence. Metabolic reconstruction analysis allowed prediction of relative abundance of microbial metabolic pathways and revealed differences between samples that cluster on the basis of the severity of AMD pollution. Global metabolic activity was predicted to be significantly higher in unpolluted and wetland sediments in contrast to polluted river sediments, indicating a metabolic stress response to AMD pollution. This is one of the first studies to explore microbial community structure dynamics within a natural wetland exposed to AMD and our findings indicate that wetland ecosystems play critical roles in maintaining diversity and metabolic structure of sediment microbial communities subject to high levels of acidity and metal pollution. Moreover, these microbial communities are predicted to be important for the remediation action of the wetland.